INFLUENCE OF DEPOSITION TIME ON ELECTRODEPOSITED NICKEL SELENIDE (NiSe2) THIN FILMS FOR SOLAR/PHOTOELECTROCHEMICAL CELLS - Anand, T.J.S.; Rajan, R.K.M.; Kasim, M.S.; Ho, S.M.; Kumar, R.T.R. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
The present study investigates the role of deposition time on the structural, morphological, compositional, optical and semiconducting properties of electrodeposited NiSe2 thin films. Nickel Selenide (NiSe2) is a transition metal chalcogenide material suitable for its good chemical and optical properties. The films were deposited on Indium Tin Oxide (ITO) coated conducting glass substrates at deposition times between 10 – 30 minutes with the interval of 5 minutes. The structural analysis of the films reveals the polycrystalline nature with sharp and high intense peaks. Scanning electron micrographs (SEM) reveals that grains are in spherical shape, uniform and pin-hole free. Composition analyses through energy dispersive X-ray (EDX) studies confirm the presence of Se and Ni to its stoichiometry. The observed direct bandgap films reduced their energy gap values from 1.30 to 1.15 eV as the deposition time increases found by optical studies. Heat treatment of these films is annealed at 200◦C for 1 hour yield the high crystallinity that also confirms by X-ray diffraction. Annealed films with longer deposition time of 30 minutes shown cracks in the surface observed by SEM. The energy gap reduced in 20% for the annealed films. This investigation confirms that the deposition time has greater influences for the grown films.